Znaczenie interwencji w prawie karnym skarbowym - Nych, Edmund (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
The article includes an assessment of the legal regulation of the Fiscal Penal Code concerning the institution of intervention. The intervention is aspecific institution that protects the right to property in fiscal penal law, because on its basis the owner can recover their items, obtained by another person by means of, for example, the offense of smuggling. The person laying aclaim is aparty to the proceedings. The author analyses the most important problems and in the summary of the article he presents the conclusions. The paper shows that the institution of intervention constitutes a reasonable forfeiture limit in the Fiscal Penal Code.
Keywords: przepadek; instytucja interwencji; ochrona mienia; kodeks karny skarbowy